Comparing Fracture Resistance of Monolithic Zirconia Crowns Designed with three Different Thicknesses: An In Vitro Study - Safa M. Alzoubi; Abdel Ghani Alsahhar; Ebtisam Alsalameh (Hungarian Dental Association, 2022)
A limited available inter-occlusal space has always been a challenge for many dental practitioners, which hinders acquiring aesthetic restorations while conserving the remaining dental structure. This research aims to analyze the relationship between the occlusal thickness of second-generation CAD/CAM monolithic zirconia restorations, and their fracture resistance, in order to determine the feasibility of reducing the occlusal thickness - particularly in the posterior oral area, where a limited inter-occlusal space is usually available, and high biting forces are usually applied. Thirty monolithic zirconia crowns were made using second generation zirconia block with different design settings that divided them into 3 groups (n = 10) according to the occlusal thickness of the restorations: Group A: 2 mm, Group B: 1.5 mm, Group C: 1 mm. Thirty designed crowns were cemented to extracted prepared natural upper premolars using glass ionomer cement, then they were tested. Fracture resistance of the monolithic zirconia crowns was significantly influenced by the occlusal thickness, the resistance improved steadily as the thickness increased. Nevertheless, the occlusal thickness could be reduced down to 1 mm and the monolithic zirconia restoration would still own sufficient resistance to tolerate the maximum natural human biting loads of the posterior oral regions.